Markers of enterocyte damage in celiac disease in children: is there an association with the clinical manifestations of the disease? - Geller, Svetlana; Umarnazarova, Zulhumor; Azimova, Noiba; Usmonova, Kamola; Kamilova, Altinoy (Frontiers in Pediatrics, 2025)
ActualityThe state of the intestinal barrier has crucial importance in the pathogenesis of celiac disease (CD). Fecal zonulin (FZ) and intestinal fatty acid binding protein (i-FABP) are important components in maintaining physiological processes in the intestine and potential biomarkers of enterocyte damage.Aim of studyTo evaluate FZ and i-FABP levels as markers of small intestine injury in children with CD, depending on the clinical forms and histomorphological changes in the small intestinal mucosa.Materials and methodsIn 2021–2023 yy, a single-center observational study was conducted among children with newly diagnosed CD.The level of FZ in stool and I-FABP in serum were determined using the Immundiagnostik ELISA kits (Germany).ResultsStudy included 75 patients,control group was 37 healthy children. The intestinal form of the CD was established in 51 (68.0%) patients,the remaining 24 (32.0%) children have CD with extraintestinal manifestations. Among children with classical CD, the mean values of FZ were 157.9 ± 29.8 ng/ml (p < 0.02 with control), in second group the mean values of FZ were 136.7 ± 17.0 ng/ml, (p < 0.05 with the control), and a statistically significant difference between the groups was p < 0.02. The i-FABP values in the first group were 2476.9 ± 297.4 pg/ml (p < 0.05 with control),and in the second −2061.47 ± 291.5 pg/ml. In the group of children with intestinal manifestations of CD, a weak positive correlation relationship was found between FZ and stool frequency (r = 0.35). In the second group: weak inverse correlations were between FZ and weight, and height (r = −0.37 and r = −0.36 respectively). I-FABP values in the first group moderately correlated with stool frequency (r = 0.53). In the group with extraintestinal manifestations, a moderate negative relationship was found between the i-FABP2 level and BMI (r = −0.53) and a moderate positive relationship between the i-FABP level and antibodies to tissue transglutaminase IgA (r = 0.58) and a weak positive correlation with histological assessment according to Marsh criteria (r = 0.34).ConclusionsOur study demonstrated a relationship between the clinical manifestations of CD and the levels of FZ and i-FABP. The increase in the values also can serve as marker of increased permeability and damage of the intestinal barrier, which will open up new possibilities for understanding the processes of restoration of the small intestinal mucosa.